Recycling and Modifications of Firearms in Central Europe during the Medieval and Post-Medieval Period - Piotr Strzyż (Fasciculi Archaeologiae Historicae, 2019)
Ancient firearms from both Medieval and Post-Medieval times were fairly often damaged in various ways. Depending on the degree of barrel damage, remains could be reused as material for making new weapons or, if the damage was minor, the weapon could be restored to full combat efficiency. Also in the case of obsolete specimens, attempts were made at modernising them e.g. by placing them on a new stock or mounting a newer type of lock. Lastly, we also see cases of barrel modifications which change the character of the weapon, e.g. from hand-held to light artillery. It seems that all these modifications were aimed at the immediate improvement of castle or town arsenals without investing significant amounts of money. Numerous examples to confirm such recycling are provided by finds of ancient firearms in museum collections in Central Europe.